Meningkatkan Indeks Penjualan melalui E-Commerce Studi Kasus Penerapan PrestaShop pada New Harapan Jaya - Surbakti, M. Aufa Nayaka Fathan; Harahap, Syaiful Zuhri (Journal of Student Development Information System (JoSDIS), 2025)
This research aims to measure the effectiveness of using the PrestaShop e-commerce platform in increasing the sales index at the New Harapan Jaya company. This case study includes an analysis of the company's initial conditions, the PrestaShop implementation process, as well as an evaluation of the results achieved after implementation. This research shows that PrestaShop has great potential to increase online sales. Apart from that, this research also identifies a number of factors that need to be considered in the e-commerce implementation process, such as feature selection, display optimization, and digital marketing strategy. It is hoped that the results of this research can contribute to the development of knowledge in the field of e-commerce and provide recommendations for companies that want to improve their sales performance through e-commerce platforms.